Stratigraphic Analysis and Depositional History of Kubang Area, Cianjur Regency, West Java - Kevin Nabil Hibatullah; Yogie Zulkurnia Rochmana (Jurnal Geosains dan Remote Sensing, 2024)
Kubang area, Cianjur Regency, West Java, is composed of well-preserved sedimentary rock formations, especially along the Cibeet River, which borders Bogor and Cianjur. This study aims to identify, reconstruct, and make models of the geological history in the research area from a stratigraphic perspective. The method used in this research consists of field observation, fossil analysis, and measuring sections, and making geological model. The data were analyzed, combined, interpreted, and simulated to become a depositional history model. Based on the results of the stratigraphic strata in the research location, the order of formations from oldest to youngest is Jatiluhur Formation of Marl and Quartz Sandstone Member (Mdm), Cantayan Formation of Breccia Member (Mttb), Cantayan Formation of Claystone Member (Mttc), Cantayan Formation of Sandstones Member (Mtts), Mangerit Intrusion (Ma), Limo Volcanic Deposits (Qyk), and Alluvial Deposits (Qa). The sedimentation process began in the Early Miocene and continues to the present. Past depositional processes in the Neritic environment were dominated by transgression-regression accompanied by volcanism played an important role, so unique and repetitive lithological units formed. This research contributes to understanding the history of deposition in the Kubang area and provides information for future research.